Strong stability measures for multicriteria quadratic integer programming problem of finding extremum solutions - Vladimir Emelichev; Yury Nikulin (Computer Science Journal of Moldova, 2018)
We consider a wide class of quadratic optimization problems with integer and Boolean variables. In this paper, the lower and upper bounds on the strong stability radius of the set of extremum solutions are obtained in the situation where solution space and criterion space are endowed with various Hölder's norms.